Mobilization of the gentamicin resistance gene in Enterococcus faecalis. - Hodel-Christian, S L (1990)
Enterococcus faecalis plasmid pBEM10 (a conjugative plasmid encoding beta-lactamase production and gentamicin resistance [Gmr]) was made transfer deficient by using Tn917. Relocation of the Gmr determinant into two sites on pCF10 was observed. Restriction analysis revealed insertion of a common 2.5-kilobase-pair HindIII and a 3.9-kilobase-pair HaeIII fragment encoding Gmr, suggesting that this determinant resides on a transposon similar to Tn4001.